A predictive model of bowel resection for incarcerated inguinal hernia based on the systemic immune-inflammation index - Chen, Lei; Chen, Lei; Wang, Ying-ying; Zhang, Li-xiang; Xia, Xiao-gang (Frontiers in Surgery, 2022)
Background and Purpose An inguinal hernia is a common surgical disease. Once incarcerated or strangulated, it may endanger the life of the patient. Therefore, it is essential to study the risk factors of incarcerated inguinal hernia (IIH) and strangulated inguinal hernia (SIH). One of the serious complications of IIH and SIH is intestinal necrosis, which occurs owing to blood supply disorder.The study explores the risk factors of intestinal resection and establishes a simple model to assess the incidence of intestinal resection to provide significant assistance and limited guidance for clinical work.Patients and Methods Our research team collected and retrospectively analysed the clinical data of 338 patients with IIH who were hospitalized in the First Affiliated Hospital of Wenzhou Medical University between September 2008 and December 2016. According to the surgical plan, we divided the included cases into two groups, non-intestinal and intestinal resection groups, and the clinical case characteristics of these groups were statistically analysed.ResultsBased on multivariable logistic regression analysis, we found that increased risk of bowel resection was highly correlated among the elderly (≥ 70 years), and for people with high temperature (≥ 37.3℃), high systemic immune-inflammation index(SII) values (≥ 1230.13), presence of bowel obstruction, and signs of peritonitis. Further, we processed the five independent risk factors using special software to obtain a simple model called a nomogram. To verify the nomogram's accuracy and predictive ability, we calculate the C-index:0.806 and use the calibration curve to evaluate its stability and predictive performance. We constructed the ROC curve nomogram and other sub-variables, and calculated the area under the curve (AUC) corresponding to the nomogram (AUC = 0.808, 95% CI=0.762to0.848), SII (AUC=0.752, 95% CI=0.703to0.797), age (AUC=0.641, 95% CI=0.587to0.692), temperature (AUC=0.579, 95% CI=0.524to0.632), bowel obstruction (AUC=0.685, 95% CI=0.633to0.734), and signs of peritonitis (AUC=0.580, 95% CI=0.525 to 0.633).Conclusion It can be said that we found for the first time that clinical variables such as SII are independent risk factors for enterectomy for IIH. The nomogram based on SII and other variables can accurately and easily predict the probability of IIH requiring bowel resection.